2020
DOI: 10.16910/jemr.12.8.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a visual tracking intervention on attention and behavior of attention deficit hyper activity children

Abstract: Attention deficit hyperactivity disorder is characterized by several cognitive and behavioral problems such as inattention and impulsivity, abnormal control of eye movements and relocation, visual fixation and visuospatial perception. There is a link between core motor functions such as oculomotor function and cognition to the extent that the oculomotor system acts as a mediator between the motor and cognitive functions. Therefore, the effects of eye-tracking intervention were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…They recruited 39 boys aged 6 to 10 years, randomized to receive the intervention (control group), and the intervention was accompanied by visual tracking movements (experimental group). The results of the experiment revealed a significant increase in the mean score of cognitive problems in children (p < 0.01) and a relative link between the motor-ocular muscle function of the visual system and cognitive function [38].…”
Section: Comparative Analysis Of Differences In Visual Attention Betw...mentioning
confidence: 90%
“…They recruited 39 boys aged 6 to 10 years, randomized to receive the intervention (control group), and the intervention was accompanied by visual tracking movements (experimental group). The results of the experiment revealed a significant increase in the mean score of cognitive problems in children (p < 0.01) and a relative link between the motor-ocular muscle function of the visual system and cognitive function [38].…”
Section: Comparative Analysis Of Differences In Visual Attention Betw...mentioning
confidence: 90%
“…Some emerging studies have provided some support for the efficacy and potential of eye-tracking-based training as a cognitive intervention 26 40 . In particular, studies reported positive effects on improving attention, memory and executive functions in post-stroke patients 29 , 30 , significant improvement in attention and impulsivity in children with ADHD 26 , 28 , improvement in reading 31 , 38 , comprehension 31 , executive function 40 , visual attention and verbal memory 39 in children with dyslexia, reduction in repetitive behaviors 35 , and improvement in visual sustained attention 33 and emotion recognition 36 in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploring suitable attention improvement methods between work and study intervals has positive signi cance for improving the e ciency of people's work and study. Many studies have revealed that attention level in childhood is signi cant to the development of physical and mental health; moreover, cultivation of attention in childhood has a positive impact on the stability of attention, attention span, attention distribution, and attention transfer in adulthood [4]. Numerous empirical studies have shown that physical activity contributes to the overall health of the human body, reduces stress, improves mood, and is advantageous in maintaining long-term concentration [5].…”
Section: Introductionmentioning
confidence: 99%